0997 The Sleep Disturbance Scale For Children In Youth With Tourette'S Disorder. (27th May 2020) - Montalbano, G E; Rozenman, M; Peris, T; Tan, P; Piacentini, J; Ricketts, E
Abstract: Introduction: Sleep disturbance is common in youth with Persistent Tic Disorders (PTDs), including Tourette's Disorder. However, studies elucidating the nature of sleep problems in PTDs are limited. The present study examines the types of sleep disturbance present in youth with PTDs relative to healthy controls, and investigates the relationship between sleep disturbance and tic severity. Methods: Participants were 56 youth ages 8 to 17 (M=11.9, SD=2.86), including individuals with PTDs (n=27), and healthy controls (n=29). An interviewer evaluated psychiatric diagnosis using the Anxiety Disorders Interview Schedule, and tic severity using the Yale Global Tic Severity Scale (YGTSS). Parents rated sleep using the Sleep Disturbance Scale for Children (SDSC), and tic severity using the Parent Tic Questionnaire (PTQ). Independent-samples t-tests and bivariate correlations were performed. Results: Higher SDSC Total scores, t(30)=-3.74, p=.001) were found in youth with PTDs relative to healthy controls. Youth with PTDs endorsed elevated sleep disturbance with respect to: Disorders of Initiating and Maintaining Sleep, t(35)=-2.43, p=.02), Sleep-Wake Transition Disorders, t(37)=-3.04, p=.004), and Disorders of Excessive Somnolence, t(33)=-2.36, p=.02). No significant group differenceswere shown for Sleep Breathing Disorders, Disorders of Arousal, and Sleep Hyperhydrosis. There was a positive association between SDSC Total scores and YGTSS Total (p=.01, r=.56) and YGTSS Impairment scores (p= .03, r=.33). Finally, there was a positive relationship between SDSC Total and PTQ Total scores (p=.01, r=.61). Conclusion: Findings suggest youth with PTDs are more likely to experience sleep disturbance than healthy children, particularly difficulties with sleep initiation and maintenance, abnormal movements during sleep, and daytime sleepiness. Further, there is a relationship between sleep disturbance and tic severity. Findings highlight the need for sleep screening and targeted sleep intervention in youth with PTDs. Support: N/A